Black ginseng: a novel medicine for treating heart failure - Dou, Peiyuan; Liu, Linlin; Jin, Mozhu; Huang, Jing; Lekhooa, Rose Makhotso; Ran, Xiaoku; Yan, Xiaohui (Frontiers in Pharmacology, 2024)
Black ginseng (BG) was processed by "steaming and drying (generally nine times)" repeatedly to produce "rare saponins" and secondary ginsenosides. This study aims to investigate the effects of BG and its components on HF to elucidate the active substances and their underlying mechanisms in the treatment of HF. The effects of BG and its fractions induced HF were explored and steroids belonging to HPA and HPG axes were determined quantitatively with a UPLC-QqQ-MS/MS method.In addition, 16S rDNA sequencing was performed on gut microbiota, followed by GC-MS analysis of SCFAs, the biochemical indexes related to energy metabolism and serum cyclic nucleotide system were also analyzed by ELISA. Based on a thorough evaluation of energy metabolism and the endocrine system, it was observed that the effects of BG components on the HPT and the HPA were more pronounced. Notably, the treatment efficacy of TSFL, WD, and PSFH was superior based on pharmacodynamic indicators such as BNP, CK, and E2/T. Furthermore, WD and BG components exhibited significant effects on androgens (T, A4). The TSFL group exerts an anti-inflammatory effect by regulating Lactobacillus/ Erysipelotrichale. The WD, PSFH, and TSFL may impact inflammatory cytokines through the gut microbiota (Lactobacillus/ Erysipelotrichale) and their metabolites (acetate, butyrate), exerting an anti-inflammatory effect. All the BG and its split components demonstrated varying levels of efficacy in alleviating HF, and TSF and PSF exhibited a significant protective effect on HF. The main active components in TSF were revealed to be ginsenoside Rk1, Rk3, 20-(S)-Rg3, 20-(S)-Rh2 by the H9C2 cell experiment. The decoction of BG and its components exhibit a potent impact on androgen hormones, with an elevation trend. This phenomenon may be attributed to the activation of the eNOs-NO pathway through androgen regulation, thereby contributing to its anti-HF. The WD, PSFH, and TSFL may exert anti-inflammatory effects through the intestinal flora (Lactobacillaceae/erysipelosiaceae) and its metabolites (acetic acid, butyric acid), which affect inflammatory factors. Our research first reported that the E2/T is related to HF and can be used as an indicator to evaluate HF.